Clinical and pathological aspects of anaplastic sarcoma with giant cells in a feline with inguinal lymph node metastasis: case report (Research, Society and Development, 2022)
Anaplastic sarcoma is considered a histological variant of the feline application sarcoma entity and may be related to drug injections. Therefore, this objective work relates to a case of anaplastic giant cell sarcoma in the right region in a feline with the presence of metastasis in the right inguinal lymph node, emphasizing its clinical and pathological findings. The patient came to the service complaining of an increase in volume in the right flank region, with evolution of 40 days and progressive growth. Aspiration cytology. result suggestive of giant cells Laboratory and imaging tests were also performed to rule out possible metastases. In addition to the lymphadenectomy performed, there is a need for local lymphadenectomy. for cells and lymph node examinations were confirmed for histopathological examination giants with inguinal lymph nodes. After the surgical procedure presented local recurrence, for personal reasons, the tutor chose not to perform new integrated resection procedures and not perform adjuvant therapies for tumor control, being performed therapies to support the patient's quality of life. In this way, it is concluded that all clinical procedures must be performed in all clinical imaging exams, cytology even more their clinical conduct before all surgical procedures.